2023
DOI: 10.3390/urbansci7020054
|View full text |Cite
|
Sign up to set email alerts
|

Promoting Urban Farming for Creating Sustainable Cities in Nepal

Abstract: This paper responds to the research question, “can urban farming in Nepal help create sustainable cities?” Especially after the COVID-19 pandemic, urban residents have begun to realize that food transported from long distances is not always reliable. Urban farming can help produce fresh food locally and help urban residents become self-reliant by engaging in healthy eating habits and practicing sustainable agricultural techniques in food-desert areas, while creating a positive impact on the environment through… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…This could be related to the experience of growing their own food at a time when they were working from home and the inability to participate in a large number of activities outside the household, as well as the reduced food supply in markets due to transportation problems, as also noticed by Chari et al [44]. Similarly, Bhattarai and Adhikari [6] stated that since the coronavirus pandemic, people who lived in urban settlements have begun to realize that the delivery of food from distant areas is not always reliable, which indisputably affects the provision of different food products. The results are in line with the findings of Lindsay et al [45], who found that the COVID outbreak had changed people's consumption practices and engagement in different activities not practiced before, such as bread baking, food growing and bicycle riding.…”
Section: Investigation Of Citizens' Familiarity With Food Production ...mentioning
confidence: 94%
See 1 more Smart Citation
“…This could be related to the experience of growing their own food at a time when they were working from home and the inability to participate in a large number of activities outside the household, as well as the reduced food supply in markets due to transportation problems, as also noticed by Chari et al [44]. Similarly, Bhattarai and Adhikari [6] stated that since the coronavirus pandemic, people who lived in urban settlements have begun to realize that the delivery of food from distant areas is not always reliable, which indisputably affects the provision of different food products. The results are in line with the findings of Lindsay et al [45], who found that the COVID outbreak had changed people's consumption practices and engagement in different activities not practiced before, such as bread baking, food growing and bicycle riding.…”
Section: Investigation Of Citizens' Familiarity With Food Production ...mentioning
confidence: 94%
“…Although practiced since cities' emergence, the production of food in some contemporary dense and high-rise-filled urban areas is not always residents' first-choice activity [6].…”
Section: Introductionmentioning
confidence: 99%
“…However, over time, such functional relationships have been weakened because core urban dwellers started consuming imported goods from far away. The COVID-19 pandemic alerted urban planners that the weakening supply chain is not a sustainable path of urban management (Bhattarai and Adhikari, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…In recent days, the concept of an isolated state coined by von Thunen has become obsolete with the development of modern transportation along with truck farming. However, Covid-19 disrupted the supply chain of food making-urban farming more attractive (Bhattarai and Adhikari, 2023). Promoting local functional specializations with advanced technology can help create circular economies and strengthen connections between rural jurisdictions and urban areas (Minnesota History, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Facilitating urban-suburban integration with space-efficient solutions: By addressing space constraints in urban homes, where rooftop availability is limited due to the proliferation of flats and multi-story structures, community solar and wind projects serve as a crucial bridge. By capitalizing on the comparatively larger roof spaces in suburban homes, these projects harmonize urban and suburban areas, ensuring efficient and equitable utilization of available space for sustainable energy generation [54].…”
mentioning
confidence: 99%